Sphingolipids as Emerging Mediators in Retina Degeneration - Simón, M. Victoria; Prado Spalm, Facundo H.; Vera, Marcela S.; Rotstein, Nora P. (Frontiers in Cellular Neuroscience, 2019)
The sphingolipids ceramide (Cer), sphingosine-1-phosphate (S1P), sphingosine (Sph) and ceramide-1-phosphate (C1P) are key signaling molecules that regulate major cellular functions. Their roles in the retina have gained increasing attention during the last decade since they emerge as mediators of proliferation, survival, migration, neovascularization, inflammation and death in retina cells. As exacerbation of these processes is central to retina degenerative diseases, they appear as crucial players in their progression. This review analyzes the functions of these sphingolipids in retina cell types and their possible pathological roles. Cer appears as a key arbitrator in diverse retinal pathologies; it promotes inflammation in endothelial and retina pigment epithelium (RPE) cells and its increase is a common feature in photoreceptor death in vitro and in animal models of retina degeneration; noteworthy, inhibiting Cer synthesis preserves photoreceptor viability and functionality. In turn, S1P acts as a double edge sword in the retina. It is essential for retina development, promoting the survival of photoreceptors and ganglion cells and regulating proliferation and differentiation of photoreceptor progenitors. However, S1P has also deleterious effects, stimulating migration of Müller glial cells, angiogenesis and fibrosis, contributing to the inflammatory scenario of proliferative retinopathies and age related macular degeneration (AMD). C1P, as S1P, promotes photoreceptor survival and differentiation. Collectively, the expanding role for these sphingolipids in the regulation of critical processes in retina cell types and in their dysregulation in retina degenerations makes them attractive targets for treating these diseases.